ROLLER RIG TESTING AT THE CZECH TECHNICAL UNIVERSITY - Kalivoda, J.; Bauer, P. (Science and Transport Progress, 2016)
Purpose. Although the advancements in computer simulation technology have paved way to provide very reliable simulation results, track tests still play an essential role during the process of development and homologation of any railway vehicle. On the other hand, track tests depend on weather conditions, are difficult to organize and are not suitable for testing vehicles in critical situations. On a roller rig, the tested vehicle is longitudinally fixed and a track is replaced by rotating rollers. Such device offer testing of railway vehicle running dynamics in safe and stable laboratory environment. The purpose of an article is to investigate and describe roller rig testing at the Czech technical university in Prague (CTU). Methodology. In the paper it is shown the history of development of the scaled CTU roller rig from the earlier stages until the current projects for which the CTU roller rig is utilized for. The current design of the experimental bogie, roller rig, sensors instrumentation and types of experiments conducted at the CTU roller rig are described in more detail. Findings. Although the differences in vehicle behaviour on a track and a scaled model on a roller rig are not negligible, scaled roller rig experiments are found as a relatively inexpensive way for verification and demonstration of computer simulations results. They are especially useful for verification of multibody system simulations (MBS) of entirely new running gear concepts. Originality. The CTU roller rig is currently used for the experiments with active controlled wheelset guidance. According to simulations results published in many papers such systems offer, in principle, better performance compared to conventional passive vehicles. However, utilization and testing of active controlled wheelset guidance on vehicles is still rare. CTU roller rig serves as a tool to verify computer simulations and demonstrate benefits of active wheelset guidance. Practical value. Experiments conducted on the CTU roller rig confirm the possibility to significantly influence railway vehicle running dynamics by actively controlled wheelset guidance. Such concept could be regarded as a possible and likely approach for the design of future railway vehicles running gears.